ESSAY TECHNOLOGY FOR THE DEVELOPMENT OF LEXICAL COMPETENCE IN MOTHER LANGUAGE CLASSES - Ahmadjonova Nilufaroy (International Journal of Literature and Language Studies, 2026)
The article analyzes the methodical basis of directing the essay writing process to the development of lexical competence. A methodological model consisting of the stages of lexical preparation, sample analysis, independent writing and reflection is developed, and the system of lexical-stylistic exercises is described.